2016
DOI: 10.1002/jbio.201600016
|View full text |Cite
|
Sign up to set email alerts
|

Low‐level laser therapy stimulates bone metabolism and inhibits root resorption during tooth movement in a rodent model

Abstract: This study evaluated the biological effects of low-level laser therapy (LLLT) on bone remodeling, tooth displacement and root resorption, occurred during the orthodontic tooth movement. Upper first molars of a total of sixty-eight male rats were subjected to orthodontic tooth movement and euthanized on days 3, 6, 9, 14 and 21 days and divided as negative control, control and LLLT group. Tooth displacement and histomorphometric analysis were performed in all animals; scanning electron microscopy analysis was do… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
66
0
4

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 56 publications
(74 citation statements)
references
References 51 publications
4
66
0
4
Order By: Relevance
“…This study evaluated the effects of PBM on SOFAT, a novel activated T‐cell‐secreted cytokine that induces osteoclastogenesis in an independent pathway of the well‐known OPG/RANK‐L/RANK system, on tooth movement in an animal model. Also, the results showed that photobiomodulation may have an effect on these cytokines, as previously reported .…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…This study evaluated the effects of PBM on SOFAT, a novel activated T‐cell‐secreted cytokine that induces osteoclastogenesis in an independent pathway of the well‐known OPG/RANK‐L/RANK system, on tooth movement in an animal model. Also, the results showed that photobiomodulation may have an effect on these cytokines, as previously reported .…”
Section: Discussionsupporting
confidence: 87%
“…The RANK‐L/RANK/OPG system plays a fundamental role in alveolar bone remodeling during induced tooth movement, and the effects of low‐power laser irradiation are also well established. Changes in the concentrations of OPG and RANK‐L in the periodontal ligament have been observed in tissue and fluids around teeth under mechanical load and also under low‐power laser irradiation .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Force delivered by the spring was measured using a precision tensiometer and the initial force applied was 50 g, which has been considered a heavy and capable of inducing root resorption, according to Suzuki et al . .…”
Section: Methodsmentioning
confidence: 99%
“…This process results in beneficial therapeutic outcomes including but not limited to the alleviation of pain or inflammation, immunomodulation, and promotion of wound healing and tissue regeneration.^ [1]. PBM therapy was found to have multiple clinical benefits, which includes reducing pain [2][3][4][5][6][7], improving wound healing [8][9][10][11], accelerating bone healing [12][13][14][15][16][17], promoting osteointegration [18], facilitating orthodontic tooth movement [19][20][21][22][23][24][25][26], stimulating bone formation [27][28][29][30][31], and improving periodontal tissue repair and decreasing inflammation and root resorption [23,26,32]. The light sources were laser or a light-emitting diode (LED).…”
Section: Introductionmentioning
confidence: 99%